2023
DOI: 10.3390/cells12020322
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Role of Kras in Myeloid Differentiation: Engaging with Wnt/β-Catenin Signaling

Abstract: Cells of the HL-60 myeloid leukemia cell line can be differentiated into neutrophil-like cells by treatment with dimethyl sulfoxide (DMSO). The molecular mechanisms involved in this differentiation process, however, remain unclear. This review focuses on the differentiation of HL-60 cells. Although the Ras proteins, a group of small GTP-binding proteins, are ubiquitously expressed and highly homologous, each has specific molecular functions. Kras was shown to be essential for normal mouse development, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 185 publications
0
1
0
Order By: Relevance
“…Wnt signaling has been shown to be active in several tumors, including breast cancer ( 22 ). The canonical Wnt protein activates transcription of β-catenin/T-cell factor (TCF)/lymphatic enhancing factor (LEF) target genes by transducing signaling β-catenin ( 23 , 24 ). Some researchers have demonstrated that Wnt antagonists with frequent genetic and epigenetic mutations in breast cancer led to β-catenin-mediated activation of Wnt target genes, suggesting that the Wnt-catenin-β1 (CTNNB1) signaling pathway plays an important role in the oncogenic process ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wnt signaling has been shown to be active in several tumors, including breast cancer ( 22 ). The canonical Wnt protein activates transcription of β-catenin/T-cell factor (TCF)/lymphatic enhancing factor (LEF) target genes by transducing signaling β-catenin ( 23 , 24 ). Some researchers have demonstrated that Wnt antagonists with frequent genetic and epigenetic mutations in breast cancer led to β-catenin-mediated activation of Wnt target genes, suggesting that the Wnt-catenin-β1 (CTNNB1) signaling pathway plays an important role in the oncogenic process ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%